Analysis of Factors Affecting Inflation in Indonesia 2015 - 2020 - Novaldo Yanescha Putra Yanescha (Research Horizon, 2022)
Inflation is the most important indicator of the economy, and the exchange rate always tries to be lower and stay stable. If the levels are going high and become unstable, that will reflect a general and continuous increase in the prices of goods and services, weakening purchasing power of the population and thereby reducing national income. As a result, the inflation rate must be under control, and the recent growth curve is visible. This study aims to analyze the factors that affect inflation in Indonesia for the 2015-2020 period and uses the Engel Granger (ECM) model error correction test to learn about the effect of variables such as currency supply and demand, interest rates and rate of exchange on inflation. The results conclude that it has a positive and significant effect on the inflation rate in Indonesia. At the same time, the Rupiah money supply is positive and insignificant compared to Indonesia’s inflation rate.